2000
DOI: 10.1080/026520300283351
|View full text |Cite
|
Sign up to set email alerts
|

Non-carcinogenic effects of TCDD in animals

Abstract: Exposure to TCDD and related chemicals leads to a plethora of effects in multiple species, tissues, and stages of development. Responses range from relatively simple biochemical alterations through overtly toxic responses, including lethality. The spectrum of effects shows some species variability, but many effects are seen in multiple wildlife, domestic, and laboratory species, ranging from fish through birds and mammals. The same responses can be generated regardless of the route of exposure, although the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
151
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 116 publications
(29 reference statements)
2
151
0
1
Order By: Relevance
“…Numerous experimental studies showed that TCDD may suppress both humoral and cell-mediated immune responses (Birnbaum and Tuomisto 2000;Kerkvliet 2002). Inhibition of immunoglobulin secretion has been demonstrated in multiple animal species (Birnbaum and Tuomisto 2000;Nohara et al 2002;Vorderstrasse et al 2001), as well as in human lymphocytes cultivated in vitro (Sulentic et al 2000). Zober et al (1994) found an increased incidence of infectious and parasitic diseases in a small retrospective cohort study of TCDD-exposed workers, but clinical diagnoses were ill-defined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous experimental studies showed that TCDD may suppress both humoral and cell-mediated immune responses (Birnbaum and Tuomisto 2000;Kerkvliet 2002). Inhibition of immunoglobulin secretion has been demonstrated in multiple animal species (Birnbaum and Tuomisto 2000;Nohara et al 2002;Vorderstrasse et al 2001), as well as in human lymphocytes cultivated in vitro (Sulentic et al 2000). Zober et al (1994) found an increased incidence of infectious and parasitic diseases in a small retrospective cohort study of TCDD-exposed workers, but clinical diagnoses were ill-defined.…”
Section: Discussionmentioning
confidence: 99%
“…The immune system is one of its most sensitive targets (Birnbaum and Tuomisto 2000). TCDD inhibits immunoglobulin secretion and decreases resistance to bacterial, viral, and parasitic infections in exposed animals (Birnbaum and Tuomisto 2000;Holsapple et al 1991;Nohara et al 2002). In humans, increased incidence of and mortality from lymphatic tumors have been found in exposed subjects, even though there is a lack of consistency among studies (Bertazzi et al 2001;IARC 1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The aryl hydrocarbon receptor can be activated by exogenous chemicals, such as halogenated aromatic hydrocarbons, non-halogenated polycyclic aromatic hydrocarbons, and other dioxin-like chemicals (DLCs), as well as endogenous compounds, such as 6-formylindolo-[3,2-b]-carbazole, bilirubin and lipoxinA4 (Denison and Nagy, 2003;Nguyen and Bradfield, 2007). The activation of AhR by these compounds leads to regulation of the expression of a battery of genes resulting in diverse biological and toxicological effects, including dermal, hepatic, cardiac and immunotoxic response, wasting syndrome, reproductive and developmental toxicities (Beischlag et al, 2008;Flaveny et al, 2010;Birnbaum and Tuomisto, 2000;Bock, 1994).…”
Section: Introductionmentioning
confidence: 99%